(untitled) (The Review of Diabetic Studies, 2025)
This article focuses on the theoretical considerations regarding the relationship of human speech with psychological processes and its manifestation as mutually reinforcing factors. At the same time, psycholinguistic factors that arise in oral and written speech situations characteristic of humans are explained through examples of literary texts.